A kind of asphalt-based silicon-carbon composite material and its preparation method and application
By using a composite core of pitch-based porous carbon and nano-silicon in silicon-carbon materials, and coating it with a composite layer of organic lithium salts and inorganic lithium salts, the problems of low conductivity and compaction density of silicon-carbon materials are solved, and high efficiency is achieved. Improved lithium storage and fast charging performance.
Patent Information
- Application Number
- CN202411045793.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-01
AI Technical Summary
Existing silicon carbon materials have problems such as poor electronic conductivity, low compaction density and high cost in high energy density lithium-ion batteries, which are difficult to meet the needs of efficient fast charging and high compaction density.
Pitch-based porous carbon is composited with nano-silicon to form the core, and the surface is coated with a composite layer of organic lithium salts and inorganic lithium salts to improve the electronic conductivity and compaction density of the material.
It effectively improves the lithium storage performance, first-time efficiency, power performance and compaction density of silicon-carbon materials, reduces side reactions, and improves the overall performance of the material.
Smart Images

Figure CN118572093B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and specifically relates to an asphalt-based silicon-carbon composite material and a preparation method and application thereof. Background Art
[0002] Silicon-carbon materials are used in fields such as high energy density lithium-ion batteries due to their high specific capacity, high first efficiency and low full-charge expansion. However, due to the porous structure of porous carbon itself and its high specific surface area, its electronic conductivity is poor, which reduces the rate performance; at the same time, the porous carbon material itself has poor compressive resistance, which reduces the compaction density of the material. Therefore, in order to improve the fast charging performance and compaction density of silicon-carbon materials, it is necessary to coat and dope the porous carbon to improve the electronic conductivity and compaction density of the material. The current porous carbon is mainly prepared by activating biomass shells or resin-based materials. There is an uneven distribution of carbon-based framework pore structure, poor isotropy of carbon materials, and the low yield of the material makes it costly. Asphalt, as a conventional negative electrode material auxiliary material, is widely used due to its advantages such as wide material sources, high residual carbon content, high isotropy and high compaction density, but it is difficult to form a high pore volume due to the high difficulty of pore formation.
[0003] Therefore, there is an urgent need to provide a porous asphalt-based carbon material to improve the lithium storage performance of silicon-carbon materials and enhance the initial efficiency, power performance and compaction density of silicon-carbon materials. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an asphalt-based silicon-carbon composite material and its preparation method and application. The present invention utilizes the porous structure of asphalt-based porous carbon to provide expansion space for the expansion of nano-silicon, while improving the lithium storage performance of the silicon-carbon material. In addition, the composite of organic lithium salt and inorganic lithium salt in the coating layer reduces the side reaction of the silicon-carbon material. The synergistic cooperation of the core and the coating layer effectively improves the initial efficiency, power performance and compaction density of the silicon-carbon composite material.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides an asphalt-based silicon-carbon composite material, comprising an inner core and a coating layer coated on the outer surface of the inner core, wherein the inner core is formed by a composite of nano-silicon and asphalt-based porous carbon, and the material of the coating layer comprises an organic lithium salt and an inorganic lithium salt.
[0007] In the present invention, the asphalt-based porous carbon has the advantages of high compressive strength, good isotropy, low compaction density, low cost, etc., which is beneficial to improving the compaction density and dynamic properties of the silicon-carbon composite material.
[0008] The present invention utilizes the porous structure of asphalt-based porous carbon to provide expansion space for the expansion of nano-silicon, while improving the lithium storage performance of the silicon-carbon material. In addition, the composite of organic lithium salt and inorganic lithium salt in the coating layer reduces the side reaction of the silicon-carbon material. The synergistic cooperation of the core and the coating layer effectively improves the initial efficiency, power performance and compaction density of the silicon-carbon composite material.
[0009] Preferably, the pore volume of the asphalt-based porous carbon is 0.6-1.0 cm 3 / g, for example, 0.6 cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g or 1.0cm 3 / g.
[0010] In the present invention, the asphalt-based porous carbon has a high pore volume, which is conducive to the decomposition of silane gas to generate nano-silicon which is deposited in the porous structure, thereby reducing the expansion of the nano-silicon.
[0011] Preferably, the mass content of the asphalt-based porous carbon in the inner core is 40-60%, for example, 40%, 50% or 60%.
[0012] In the present invention, if the mass content of the asphalt-based porous carbon in the core is too small, the nano-silicon will expand greatly and the resistance will be high; if the mass content of the asphalt-based porous carbon in the core is too large, the specific capacity of the material will be reduced.
[0013] Preferably, the pitch-based porous carbon is doped with metal elements.
[0014] In the present invention, doping with metal elements is beneficial to reducing defects in the material, improving the electronic conductivity of the material, and obtaining a silicon-carbon composite material with excellent electrochemical properties.
[0015] Preferably, the doping amount of the metal element in the pitch-based porous carbon is 1-5wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%.
[0016] In the present invention, if the doping amount of the metal element is too small, the improvement of the electronic conductivity of the material is too small, and there is almost no change; if the doping amount of the metal element is too large, lithium carbonate and lithium hydroxide are easily generated during use, causing the material to expand and increase its alkalinity, thereby reducing the processing performance.
[0017] Preferably, the metal element includes lithium.
[0018] In the present invention, lithium, compared with other metal elements, is more conducive to forming lithium silicate with silicon, thereby improving the structural stability, initial efficiency and cycle performance of the material.
[0019] Preferably, the mass ratio of the organic lithium salt to the inorganic lithium salt is (1-3):(1-3), wherein the selection range of the organic lithium salt "1-3" can be, for example, 1, 1.5, 2, 2.5 or 3, and the selection range of the inorganic lithium salt "1-3" can be, for example, 1, 1.5, 2, 2.5 or 3, etc.
[0020] In the present invention, if the mass ratio of the organic lithium salt to the inorganic lithium salt is too small, the low temperature performance of the material will be limited; if the mass ratio of the organic lithium salt to the inorganic lithium salt is too large, the high temperature performance will be reduced.
[0021] Preferably, the organic lithium salt includes any one of lithium acetate, lithium sulfonate, lithium stearate, lithium pyruvate, lithium oxalate or lithium benzoate, or a combination of at least two thereof.
[0022] Preferably, the inorganic lithium salt includes any one of lithium niobate, lithium cerate, lithium aluminate, lithium titanate or lithium zirconate, or a combination of at least two thereof.
[0023] Preferably, based on the mass of the asphalt-based silicon-carbon composite material, the mass content of the coating layer is 5-15%, for example, 5%, 7%, 10%, 12% or 15%.
[0024] In the present invention, if the mass content of the coating layer is too small, that is, the coating layer is too thin, the effect on improving the initial efficiency and fast charging performance of the material is small, and being too thin affects the processing performance; if the mass content of the coating layer is too large, that is, the coating layer is too thick, the specific capacity of the material is reduced.
[0025] In a second aspect, the present invention provides a method for preparing the asphalt-based silicon-carbon composite material as described in the first aspect, the preparation method comprising the following steps:
[0026] (1) introducing a silicon source gas and a carbon source gas into a reaction device where the pitch-based porous carbon is located to perform co-deposition to obtain a silicon-carbon material;
[0027] (2) Alternately depositing an organic lithium compound and an inorganic lithium compound on the surface of the silicon-carbon material to obtain the asphalt-based silicon-carbon composite material.
[0028] In the present invention, the silicon source gas is decomposed to generate nano-silicon. Since the activity of nano-silicon is very strong, a carbon source gas is introduced to passivate the surface of the nano-silicon.
[0029] Preferably, the asphalt-based porous carbon in step (1) is metal-doped asphalt-based porous carbon, and the specific preparation steps include:
[0030] The oxidized asphalt, the cross-linking agent, the organic template and the organic metal compound are mixed, and pre-carbonized and activated in sequence to obtain the metal-doped asphalt-based porous carbon.
[0031] In the present invention, a crosslinking agent, an organic template and an organic metal compound are added to the oxidized asphalt, and the crosslinking agent is used to form a pore structure in the asphalt to form a high pore volume structure; at the same time, the organic metal compound volatilizes and expands the carbon layer during the carbonization process, which can increase the interlayer spacing and improve the rate performance.
[0032] Preferably, the cross-linking agent comprises any one of peroxyacetic acid, dicyclohexyl peroxydicarbonate, 3-chloroperoxybenzoic acid, tert-butyl peroxyvalerate or tert-butyl peroxybenzoate, or a combination of at least two thereof.
[0033] Preferably, the organic template includes any one of tetraethylammonium hydroxide, tetraethylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium chloride or tetramethylammonium chloride, or a combination of at least two thereof.
[0034] Preferably, the organometallic compound is an organometallic lithium compound, and the organometallic lithium compound includes any one of lithium acetate, lithium sulfonate, lithium stearate or lithium benzoate, or a combination of at least two thereof.
[0035] Preferably, the mass ratio of the oxidized asphalt, cross-linking agent, organic template and organometallic compound is 100:(5-15):(1-5):(5-15), wherein the selection range of the cross-linking agent "5-15" can be, for example, 5, 7, 10, 12 or 15, etc., the selection range of the organic template "1-5" can be, for example, 1, 2, 3, 4 or 5, etc., and the selection range of the organometallic compound "5-15" can be, for example, 5, 7, 10, 12 or 15, etc.
[0036] Preferably, a reducing gas is introduced during the pre-carbonization process.
[0037] In the present invention, the oxygen-containing groups on the surface of the oxidized asphalt generate amorphous carbon without oxygen-containing groups under the action of the reducing gas, which is beneficial to improving the initial efficiency, avoiding side reactions between the oxygen-containing groups and the electrolyte, and improving the storage performance.
[0038] Preferably, the reducing gas includes any one of carbon monoxide, hydrogen or nitric oxide, or a combination of at least two of them.
[0039] Preferably, the flow rate of the reducing gas is 100-500 mL / min, for example, it can be 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min.
[0040] Preferably, the pre-carbonization treatment temperature is 600-900°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, and the treatment time is 60-600min, for example, it can be 60min, 100min, 200min, 300min, 400min, 500min or 600min.
[0041] Preferably, carbon dioxide gas is introduced during the activation treatment.
[0042] Preferably, the flow rate of the carbon dioxide gas is 100-500 mL / min, for example, it can be 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min.
[0043] Preferably, the temperature of the activation treatment is 1000-1200°C, for example, it can be 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, and the time is 60-600min, for example, it can be 60min, 100min, 200min, 300min, 400min, 500min or 600min.
[0044] Preferably, the co-deposition temperature in step (1) is 400-600°C, for example, 400°C, 450°C, 500°C, 550°C or 600°C.
[0045] Preferably, the silicon source gas in step (1) includes any one of monosilane gas, disilane gas or trichlorosilane gas.
[0046] Preferably, the carbon source gas in step (1) includes any one of methane, ethane, acetylene, ethylene or propyne, or a combination of at least two of them.
[0047] Preferably, the volume ratio of the silicon source gas to the carbon source gas in step (1) is 10:(1-5), for example, it can be 10:1, 10:2, 10:3, 10:4 or 10:5.
[0048] In the present invention, a certain amount of carbon source gas is added to coat and passivate the nano-silicon, which is beneficial to improving the safety performance and initial efficiency of the material.
[0049] Preferably, the flow rates of the silicon source gas and the carbon source gas in step (1) are both 100-500 mL / min, for example, 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min.
[0050] Preferably, the co-deposition time in step (1) is 60-600 min, for example, it can be 60 min, 100 min, 200 min, 300 min, 400 min, 500 min or 600 min.
[0051] Preferably, the method of alternately depositing the organic lithium compound and the inorganic lithium compound in step (2) comprises atomic vapor deposition.
[0052] Preferably, the specific steps of the atomic vapor deposition method include:
[0053] The silicon-carbon material is placed in a reaction chamber, vacuumized, and then an inorganic lithium compound and an organic lithium compound are alternately introduced for cyclic deposition to form a coating layer.
[0054] Preferably, the temperature of the reaction chamber is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C.
[0055] Preferably, the number of cyclic deposition is 1-10 times, for example, it can be 1 time, 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times or 10 times.
[0056] In the present invention, the deposition of organic lithium compounds and inorganic lithium compounds is carried out alternately, which is conducive to forming a coating layer similar to an artificial SEI structure and improving the high-temperature and low-temperature properties of the material.
[0057] Preferably, the preparation method comprises the following steps:
[0058] (I) mixing oxidized asphalt, a cross-linking agent, an organic template and an organic metal compound, transferring the mixture to a tube furnace, heating the mixture to 600-900°C and introducing a reducing gas at a flow rate of 100-500 mL / min for 60-600 min of pre-carbonization, then heating the mixture to 1000-1200°C and introducing a carbon dioxide gas at a flow rate of 100-500 mL / min for 60-600 min of activation to obtain metal-doped asphalt-based porous carbon;
[0059] Wherein, the mass ratio of oxidized asphalt, cross-linking agent, organic template and organic metal compound is 100:(5-15):(1-5):(5-15);
[0060] (II) placing the metal-doped asphalt-based porous carbon in a rotary kiln, raising the temperature to 400-600° C., and simultaneously introducing a silicon source gas and a carbon source gas at a flow rate of 100-500 mL / min, and performing co-deposition for 60-600 min to obtain a silicon-carbon material;
[0061] Wherein, the volume ratio of silicon source gas to carbon source gas is 10:(1-5);
[0062] (III) placing the silicon-carbon material in a reaction chamber, evacuating the chamber to ≤0.1 Torr, and heating the chamber to 300-500°C, then sequentially introducing an inorganic lithium compound and an oxygen source gas (e.g., oxygen gas, etc.) into the reaction chamber for pre-deposition, and then sequentially introducing an organic lithium compound and an oxygen source gas (e.g., oxygen gas, etc.) into the reaction chamber for post-deposition, wherein the pre-deposition and post-deposition constitute a cycle unit, and the cycle unit is repeated 1-10 times to obtain an asphalt-based silicon-carbon composite material.
[0063] In a third aspect, the present invention provides a lithium-ion battery, wherein the negative electrode of the lithium-ion battery includes the asphalt-based silicon-carbon composite material as described in the first aspect.
[0064] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0065] Compared with the prior art, the present invention has the following beneficial effects:
[0066] (1) The present invention utilizes the pore structure of asphalt-based porous carbon to provide expansion space for the expansion of nano-silicon, while improving the lithium storage performance of silicon-carbon materials. In addition, the composite of organic lithium salt and inorganic lithium salt in the coating layer reduces the side reaction of silicon-carbon materials. The synergistic cooperation between the core and the coating layer effectively improves the initial efficiency, power performance and compaction density of the silicon-carbon composite material.
[0067] (2) The lithium-ion battery prepared based on the silicon-carbon composite material provided by the present invention has excellent power performance, rate performance and high-temperature storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is a SEM image of the asphalt-based silicon-carbon composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0069] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0070] Example 1
[0071] This embodiment provides a pitch-based silicon-carbon composite material, the pitch-based silicon-carbon composite material comprising a core and a coating layer coated on the outer surface of the core, the core is formed by a composite of nano-silicon and pitch-based porous carbon, and the material of the coating layer comprises an organic lithium salt and an inorganic lithium salt;
[0072] The pore volume of the pitch-based porous carbon is 0.8 cm 3 / g, the mass content of the asphalt-based porous carbon in the inner core is 49%, the asphalt-based porous carbon is doped with lithium, and the doping amount of the lithium is 3wt%;
[0073] The mass ratio of the organic lithium salt to the inorganic lithium salt is 1:1, the organic lithium salt is lithium acetate, the inorganic lithium salt is lithium niobate, and based on the mass of the asphalt-based silicon-carbon composite material, the mass content of the coating layer is 10%.
[0074] This embodiment also provides a method for preparing the above-mentioned asphalt-based silicon-carbon composite material, and the preparation method comprises the following steps:
[0075] (1) 100 g of oxidized asphalt, 10 g of a cross-linking agent, 3 g of an organic template and 10 g of an organic metal lithium compound were mixed and transferred to a tube furnace, heated to 800 °C and introduced with hydrogen at a flow rate of 300 mL / min for 300 min of pre-carbonization, then heated to 1100 °C and introduced with carbon dioxide at a flow rate of 300 mL / min for 300 min of activation treatment to obtain metal-doped asphalt-based porous carbon;
[0076] The mass ratio of oxidized asphalt, cross-linking agent, organic template and organometallic lithium compound is 100:10:3:10, the cross-linking agent is peroxyacetic acid, the organic template is tetraethylammonium hydroxide, and the organometallic lithium compound is lithium acetate;
[0077] (2) placing the metal-doped asphalt-based porous carbon in a rotary kiln, raising the temperature to 500° C., and simultaneously introducing a silicon source gas and a carbon source gas at a flow rate of 300 mL / min, and performing co-deposition for 300 min to obtain a silicon-carbon material;
[0078] The volume ratio of the silicon source gas to the carbon source gas is 10:3, the silicon source gas is monosilane gas, and the carbon source gas is methane;
[0079] (3) The silicon-carbon material is placed in a reaction chamber, evacuated to ≤0.1 Torr, and heated to 400°C, and then the inorganic lithium salt and the organic lithium salt are deposited according to the following steps: (a) an inorganic lithium compound is introduced into the reaction chamber for 0.3 s; (b) nitrogen is purged for 60 s; (c) oxygen is introduced into the reaction chamber for 5 s; (d) nitrogen is purged for 5 s; (e) water vapor is introduced into the reaction chamber for 0.03 s; (f) nitrogen is purged for 50 s; (g) an organic lithium compound is introduced into the reaction chamber for 0.3 s; (h) nitrogen is purged for 60 s; (i) oxygen is introduced into the reaction chamber for 5 s; (j) nitrogen is purged for 5 s; (k) water vapor is introduced into the reaction chamber for 0.03 s; (l) nitrogen is purged for 50 s. The above steps are recorded as a cycle unit. The cycle unit is repeated 5 times to obtain a pitch-based silicon-carbon composite material.
[0080] Among them, the inorganic lithium compound is lithium niobate, and the organic lithium compound is lithium acetate.
[0081] Figure 1 The SEM image of the asphalt-based silicon-carbon composite material prepared in this embodiment is shown. It can be seen from the figure that the asphalt-based silicon-carbon composite material has a granular structure, and the material particle size is evenly distributed and slightly bonded, and the particle size is between 5-10 μm.
[0082] Example 2
[0083] This embodiment provides a pitch-based silicon-carbon composite material, the pitch-based silicon-carbon composite material comprising a core and a coating layer coated on the outer surface of the core, the core is formed by a composite of nano-silicon and pitch-based porous carbon, and the material of the coating layer comprises an organic lithium salt and an inorganic lithium salt;
[0084] The pore volume of the pitch-based porous carbon is 0.6 cm 3 / g, the mass content of the asphalt-based porous carbon in the inner core is 60%, the asphalt-based porous carbon is doped with lithium, and the doping amount of the lithium is 1wt%;
[0085] The mass ratio of the organic lithium salt to the inorganic lithium salt is 1:3, the organic lithium salt is lithium sulfonate, the inorganic lithium salt is lithium cerate, and based on the mass of the asphalt-based silicon-carbon composite material, the mass content of the coating layer is 5%.
[0086] This embodiment also provides a method for preparing the above-mentioned asphalt-based silicon-carbon composite material, and the preparation method comprises the following steps:
[0087] (1) 100 g of oxidized asphalt, 5 g of a cross-linking agent, 1 g of an organic template and 5 g of an organic metal lithium compound were mixed and transferred to a tube furnace, heated to 600 °C and introduced with carbon monoxide gas at a flow rate of 100 mL / min for 600 min of pre-carbonization, then heated to 1000 °C and introduced with carbon dioxide gas at a flow rate of 100 mL / min for 600 min of activation treatment to obtain metal-doped asphalt-based porous carbon;
[0088] The mass ratio of oxidized asphalt, crosslinking agent, organic template and organometallic lithium compound is 100:5:1:5, the crosslinking agent is dicyclohexyl peroxydicarbonate, the organic template is tetraethylammonium bromide, and the organometallic lithium compound is lithium sulfonate;
[0089] (2) placing the metal-doped asphalt-based porous carbon in a rotary kiln, raising the temperature to 400° C., and simultaneously introducing a silicon source gas and a carbon source gas at a flow rate of 100 mL / min, and performing co-deposition for 600 min to obtain a silicon-carbon material;
[0090] The volume ratio of the silicon source gas to the carbon source gas is 10:1, the silicon source gas is disilane gas, and the carbon source gas is acetylene;
[0091] (3) The silicon-carbon material is placed in a reaction chamber, evacuated to ≤0.1 Torr, and heated to 300°C, and then the inorganic lithium salt and the organic lithium salt are deposited according to the following steps: (a) an inorganic lithium compound is introduced into the reaction chamber for 0.3 s; (b) nitrogen is purged for 60 s; (c) oxygen is introduced into the reaction chamber for 5 s; (d) nitrogen is purged for 5 s; (e) water vapor is introduced into the reaction chamber for 0.03 s; (f) nitrogen is purged for 50 s; (g) an organic lithium compound is introduced into the reaction chamber for 0.3 s; (h) nitrogen is purged for 60 s; (i) oxygen is introduced into the reaction chamber for 5 s; (j) nitrogen is purged for 5 s; (k) water vapor is introduced into the reaction chamber for 0.03 s; (l) nitrogen is purged for 50 s. The above steps are recorded as a cycle unit. The cycle unit is repeated once to obtain a pitch-based silicon-carbon composite material.
[0092] The inorganic lithium compound is lithium cerate, and the organic lithium compound is lithium sulfonate.
[0093] Example 3
[0094] This embodiment provides a pitch-based silicon-carbon composite material, the pitch-based silicon-carbon composite material comprising a core and a coating layer coated on the outer surface of the core, the core is formed by a composite of nano-silicon and pitch-based porous carbon, and the material of the coating layer comprises an organic lithium salt and an inorganic lithium salt;
[0095] The pore volume of the pitch-based porous carbon is 1.0 cm 3 / g, the mass content of the asphalt-based porous carbon in the inner core is 40%, the asphalt-based porous carbon is doped with lithium, and the doping amount of the lithium is 5wt%;
[0096] The mass ratio of the organic lithium salt to the inorganic lithium salt is 3:1, the organic lithium salt is lithium pyruvate, and the inorganic lithium salt is lithium aluminate. Based on the mass of the asphalt-based silicon-carbon composite material, the mass content of the coating layer is 15%.
[0097] This embodiment also provides a method for preparing the above-mentioned asphalt-based silicon-carbon composite material, and the preparation method comprises the following steps:
[0098] (1) 100 g of oxidized asphalt, 15 g of a cross-linking agent, 5 g of an organic template and 15 g of an organic metal lithium compound were mixed and transferred to a tube furnace, heated to 900 °C and introduced with nitric oxide gas at a flow rate of 500 mL / min for 60 min of pre-carbonization, then heated to 1200 °C and introduced with carbon dioxide gas at a flow rate of 500 mL / min for 60 min of activation treatment to obtain metal-doped asphalt-based porous carbon;
[0099] The mass ratio of oxidized asphalt, crosslinking agent, organic template and organometallic lithium compound is 100:15:5:15, the crosslinking agent is 3-chloroperoxybenzoic acid, the organic template is tetrabutylammonium bromide, and the organometallic lithium compound is lithium stearate;
[0100] (2) placing the metal-doped asphalt-based porous carbon in a rotary kiln, heating it to 600° C., and simultaneously introducing a silicon source gas and a carbon source gas at a flow rate of 500 mL / min, and performing co-deposition for 60 minutes to obtain a silicon-carbon material;
[0101] The volume ratio of the silicon source gas to the carbon source gas is 10:5, the silicon source gas is monosilane gas, and the carbon source gas is methane;
[0102] (3) The silicon-carbon material is placed in a reaction chamber, evacuated to ≤0.1 Torr, and heated to 500°C, and then the inorganic lithium salt and the organic lithium salt are deposited according to the following steps: (a) an inorganic lithium compound is introduced into the reaction chamber for 0.3 s; (b) nitrogen is purged for 60 s; (c) oxygen is introduced into the reaction chamber for 5 s; (d) nitrogen is purged for 5 s; (e) water vapor is introduced into the reaction chamber for 0.03 s; (f) nitrogen is purged for 50 s; (g) an organic lithium compound is introduced into the reaction chamber for 0.3 s; (h) nitrogen is purged for 60 s; (i) oxygen is introduced into the reaction chamber for 5 s; (j) nitrogen is purged for 5 s; (k) water vapor is introduced into the reaction chamber for 0.03 s; (l) nitrogen is purged for 50 s. The above steps are recorded as a cycle unit. The cycle unit is repeated 10 times to obtain a pitch-based silicon-carbon composite material.
[0103] Among them, the inorganic lithium compound is lithium aluminate, and the organic lithium compound is lithium pyruvate.
[0104] Example 4
[0105] The difference between this embodiment and embodiment 1 is that the mass content of the asphalt-based porous carbon in the inner core is 30%.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 5
[0108] The difference between this embodiment and embodiment 1 is that the mass content of the asphalt-based porous carbon in the inner core is 70%.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 6
[0111] The difference between this embodiment and embodiment 1 is that the asphalt-based porous carbon is not doped with lithium, that is, no organic metal lithium compound is added in step (1).
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Comparative Example 1
[0114] The difference between this comparative example and Example 1 is that inorganic lithium salt and organic lithium salt are not deposited on the silicon-carbon material, that is, step (3) is not performed.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 2
[0117] The difference between this comparative example and Example 1 is that no organic template is added in step (1).
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 3
[0120] The difference between this comparative example and Example 1 is that the coating layer contains only organic lithium salt, that is, procedures (a) to (f) are not performed in one cycle unit of step (3).
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Comparative Example 4
[0123] The difference between this comparative example and Example 1 is that the coating layer contains only inorganic lithium salt, that is, procedures (g) to (l) are not performed in one cycle unit of step (3).
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Performance Testing
[0126] 1. The specific surface area and tap density of the asphalt-based silicon-carbon composite materials provided in the above embodiments and comparative examples were tested with reference to GB / T 38823-2020 "Silicon Carbon", and the powder resistivity of the asphalt-based silicon-carbon composite materials was tested using a four-probe tester.
[0127] 2. Button cells were made based on the asphalt-based silicon-carbon composite materials provided in the above embodiments and comparative examples, and their electrochemical performance was tested.
[0128] The preparation steps of button cells include:
[0129] The asphalt-based silicon-carbon composite material, polyvinylidene fluoride, conductive carbon black and N-methylpyrrolidone are stirred and mixed to obtain a negative electrode slurry; wherein the mass volume ratio of the asphalt-based silicon-carbon composite material, conductive carbon black, polyvinylidene fluoride and N-methylpyrrolidone is 90g:4g:6g:250mL; the negative electrode slurry is coated on a copper foil, dried and rolled to obtain a negative electrode sheet; LiPF6 is used as an electrolyte in the electrolyte, the concentration of the electrolyte is 1 mol / L, and a mixture of ethylene carbonate and diethyl carbonate with a volume ratio of 1:1 is used as a solvent; the metal lithium sheet is used as a counter electrode, and the diaphragm is a polypropylene film. The button cell assembly is carried out in an argon-filled glove box.
[0130] The button cell was assembled on a Blue Power CT2001A battery tester for electrochemical performance testing, with a charge and discharge voltage range of 0.005 V to 2.0 V and a charge and discharge rate of 0.1 C. In addition, the rate performance was also tested, i.e., charging at 1 C and discharging at 0.1 C.
[0131] The thickness D1 of the negative electrode sheet of the button battery after rolling is tested, and then the button battery is fully charged to 100% SOC, the negative electrode sheet is dissected, and its full-charge thickness D2 is tested, and then the expansion rate is calculated, and the expansion rate is = (D1-D2) / D1×100%.
[0132] The above test results are shown in Table 1.
[0133] Table 1
[0134]
[0135] It can be seen from the above table that the asphalt-based silicon-carbon composite material provided by the present invention has excellent specific capacity, first efficiency, powder resistivity, full-charge expansion and rate performance. The reason is that: doping metallic lithium in asphalt-based porous carbon can effectively improve the electronic conductivity of the material, reduce polarization, improve rate performance, and the high pore volume can effectively reduce the expansion of silicon; at the same time, coating the surface of the inner core with organic lithium salts and inorganic lithium salts can significantly reduce the loss of lithium ions during the first discharge process, improve the first efficiency, and restrain the expansion of silicon during the charge and discharge process.
[0136] It can be seen from Examples 1 and 4-5 that if the mass content of asphalt-based porous carbon in the inner core is too small, it will easily cause large expansion of nano-silicon and high resistance, leading to a decrease in material performance; if the mass content of asphalt-based porous carbon in the inner core is too large, the specific capacity of the material will be reduced.
[0137] It can be seen from Examples 1 and 6 that if lithium is not doped into the asphalt-based porous carbon, the structural stability, initial efficiency and cycle performance of the material cannot be significantly improved.
[0138] It can be seen from Example 1 and Comparative Example 1 that if inorganic lithium salt and organic lithium salt are not deposited on the silicon-carbon material, the ion diffusion rate of the material will be reduced, and the expansion of the core nano-silicon cannot be restrained, resulting in a decrease in its initial efficiency and a decrease in rate performance.
[0139] It can be seen from Example 1 and Comparative Example 2 that if no organic template is added in step (1), fewer pores are formed, which reduces the lithium storage capacity, and fewer pores cause greater expansion of the material.
[0140] It can be seen from Example 1 and Comparative Examples 3-4 that if the coating layer contains only organic lithium salt, it will cause greater expansion and reduce the ion transmission rate; if the coating layer contains only inorganic lithium salt, it will cause greater expansion and reduce the ion transmission rate.
[0141] 3. A soft-pack battery is prepared based on the silicon-carbon composite negative electrode material provided in the above embodiments and comparative examples, and the specific steps include:
[0142] The asphalt-based silicon-carbon composite material and artificial graphite with a mass ratio of 5:95 are mixed to form the negative electrode sheet, which is then mixed with the positive electrode ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 The positive electrode sheet made of O2), electrolyte and separator are assembled into a 5Ah soft-pack battery; among them, the separator model is Celegard 2400, LiPF6 is used as the electrolyte in the electrolyte, the concentration of the electrolyte is 1.3mol / L, and a mixture of ethylene carbonate and diethyl carbonate with a volume ratio of 1:1 is used as the solvent.
[0143] ① Test the liquid absorption capacity and gas production of the negative electrode respectively.
[0144] A. Test of liquid absorption ability: Use a 1mL burette and absorb 1mL of electrolyte, add a drop on the surface of the negative electrode, and time it until the electrolyte is completely absorbed, and record the time t.
[0145] B. Gas production: Weigh the negative electrode and calculate the weight of the active material as m1. Then place the negative electrode in deionized water at 45°C and soak for 48 hours. Calculate the gas production volume V1. Then calculate the gas production of the negative electrode = V1 / m1.
[0146] The above test results are shown in Table 2.
[0147] Table 2
[0148]
[0149] It can be seen from the above table that the liquid absorption capacity and electrode gas production of the asphalt-based silicon-carbon composite material prepared by the present invention are reduced, and the reason may be that: the asphalt-based silicon-carbon composite material prepared by the present invention has a large specific surface area, which can effectively improve the liquid absorption and retention capacity of the material; at the same time, the organic lithium salt and the inorganic lithium salt are coated on the outer shell of the asphalt-based silicon-carbon composite material by atomic vapor deposition, which is beneficial to improve the material coating integrity and reduce gas production.
[0150] ② Conduct rate performance and high temperature storage performance tests on the soft-pack battery prepared above.
[0151] Test conditions for rate performance: HPPC tests at different SOCs (5%, 10%, 30%, 50%, 70%, 95%) are performed according to 3C to test the DC internal resistance (DCR) of the charging state.
[0152] Test conditions for high temperature storage performance test: Test the capacity of the soft pack battery at full charge at 60°C as X1, then place it at 60°C for 7 days, test the capacity of the battery again as X2, and calculate the charge retention rate = X2 / X1*100%; then charge the battery to full charge (100% SOC), test the capacity of the battery as X3, and calculate the recovery capacity = X3 / X1*100%
[0153] The above test results are shown in Table 3.
[0154] Table 3
[0155]
[0156] It can be seen from the above table that the charging DCR of the soft-pack lithium-ion battery prepared based on the asphalt-based silicon-carbon composite material provided by the present invention is lower than that of the comparative example. The reason is that the asphalt-based silicon-carbon composite material of the present invention has a low powder resistivity, which can reduce the resistance, and the outer layer of the inner core is coated with organic lithium salts and inorganic lithium salts, which can reduce the ionic impedance and thus reduce the charging DCR. In addition, the asphalt-based silicon-carbon composite material provided by the present invention has excellent high-temperature storage performance. The reason is that the surface of the material is coated with organic lithium salts and inorganic lithium salts, which can improve the coating integrity of the material, reduce gas production, reduce side reactions, and improve the high-temperature storage performance of the material.
[0157] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a pitch-based silicon-carbon composite material, characterized in that: The preparation method comprises the following steps: (1) introducing a silicon source gas and a carbon source gas into a reaction device where the pitch-based porous carbon is located to perform co-deposition to obtain a silicon-carbon material; (2) alternately depositing an organic lithium compound and an inorganic lithium compound on the surface of the silicon-carbon material to obtain the asphalt-based silicon-carbon composite material; The asphalt-based porous carbon in step (1) is metal-doped asphalt-based porous carbon, and the specific preparation steps include: mixing oxidized asphalt, a cross-linking agent, an organic template and an organic metal compound, and sequentially performing pre-carbonization and activation treatment to obtain the metal-doped asphalt-based porous carbon; The organic template includes any one of tetraethylammonium hydroxide, tetraethylammonium bromide, tetrabutylammonium bromide, tetrabutylammonium chloride or tetramethylammonium chloride, or a combination of at least two thereof; The asphalt-based silicon-carbon composite material comprises an inner core and a coating layer coated on the outer surface of the inner core, wherein the inner core is formed by a composite of nano-silicon and asphalt-based porous carbon, the asphalt-based porous carbon is doped with metal elements, and the material of the coating layer comprises an organic lithium salt and an inorganic lithium salt; The metal element includes lithium; The organic lithium salt includes any one or a combination of at least two of lithium acetate, lithium sulfonate, lithium stearate, lithium pyruvate, lithium oxalate or lithium benzoate; The inorganic lithium salt includes any one of lithium niobate, lithium cerate, lithium aluminate, lithium titanate or lithium zirconate, or a combination of at least two thereof.
2. The preparation method according to claim 1, characterized in that: The pore volume of the pitch-based porous carbon is 0.6-1.0 cm 3 / g.
3. The preparation method according to claim 1, characterized in that: The mass content of the asphalt-based porous carbon in the core is 40-60%; In the pitch-based porous carbon, the doping amount of the metal element is 1-5wt%.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the organic lithium salt to the inorganic lithium salt is (1-3):(1-3); Based on the mass of the asphalt-based silicon-carbon composite material, the mass content of the coating layer is 5-15%.
5. The preparation method according to claim 1, characterized in that: The cross-linking agent includes any one of peroxyacetic acid, dicyclohexyl peroxydicarbonate, 3-chloroperoxybenzoic acid, tert-butyl peroxyvalerate or tert-butyl peroxybenzoate, or a combination of at least two thereof; The organometallic compound is an organometallic lithium compound, and the organometallic lithium compound includes any one or a combination of at least two of lithium acetate, lithium sulfonate, lithium stearate or lithium benzoate; The mass ratio of the oxidized asphalt, the cross-linking agent, the organic template and the organic metal compound is 100:(5-15):(1-5):(5-15); During the pre-carbonization process, reducing gas is introduced; The reducing gas includes any one of carbon monoxide, hydrogen or nitric oxide, or a combination of at least two thereof; The flow rate of the reducing gas is 100-500 mL / min; The pre-carbonization treatment temperature is 600-900°C and the treatment time is 60-600min; During the activation treatment, carbon dioxide gas is introduced; The flow rate of the carbon dioxide gas is 100-500 mL / min; The activation treatment is carried out at a temperature of 1000-1200° C. and for a time of 60-600 min.
6. The preparation method according to claim 1, characterized in that: The temperature of the co-deposition in step (1) is 400-600°C; The silicon source gas in step (1) includes any one of monosilane gas, disilane gas or trichlorosilane gas; The carbon source gas in step (1) includes any one of methane, ethane, acetylene, ethylene or propyne, or a combination of at least two thereof; The volume ratio of the silicon source gas to the carbon source gas in step (1) is 10:(1-5); The flow rates of the silicon source gas and the carbon source gas in step (1) are both 100-500 mL / min; The co-deposition time in step (1) is 60-600 min.
7. The preparation method according to claim 1, characterized in that: The method of alternately depositing the organic lithium compound and the inorganic lithium compound in step (2) comprises an atomic vapor deposition method; The specific steps of the atomic vapor deposition method include: The silicon-carbon material is placed in a reaction chamber, evacuated, and then an inorganic lithium compound and an organic lithium compound are alternately introduced for cyclic deposition to form a coating layer; The temperature of the reaction chamber is 300-500°C; The number of the cyclic deposition is 1-10 times.
8. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (I) mixing oxidized asphalt, a cross-linking agent, an organic template and an organic metal compound, transferring the mixture to a tube furnace, heating the mixture to 600-900°C and introducing a reducing gas at a flow rate of 100-500 mL / min for 60-600 min of pre-carbonization, then heating the mixture to 1000-1200°C and introducing a carbon dioxide gas at a flow rate of 100-500 mL / min for 60-600 min of activation to obtain metal-doped asphalt-based porous carbon; Wherein, the mass ratio of oxidized asphalt, cross-linking agent, organic template and organic metal compound is 100:(5-15):(1-5):(5-15); (II) placing the metal-doped asphalt-based porous carbon in a rotary kiln, raising the temperature to 400-600° C., and simultaneously introducing a silicon source gas and a carbon source gas at a flow rate of 100-500 mL / min, and performing co-deposition for 60-600 min to obtain a silicon-carbon material; Wherein, the volume ratio of silicon source gas to carbon source gas is 10:(1-5); (III) placing the silicon-carbon material in a reaction chamber, evacuating the chamber to ≤0.1 Torr, and heating the chamber to 300-500°C, then introducing an inorganic lithium compound and an oxygen source gas into the reaction chamber in sequence for pre-deposition, and then introducing an organic lithium compound and an oxygen source gas into the reaction chamber in sequence for post-deposition, wherein the pre-deposition and post-deposition constitute a cycle unit, and the cycle unit is repeated 1-10 times to obtain an asphalt-based silicon-carbon composite material.
9. A lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery includes a pitch-based silicon-carbon composite material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Graphite composite electrode material and preparation method thereof
CN113675389A
Preparation method of asphalt-based silicon-carbon negative electrode material for lithium ion battery and product of asphalt-based silicon-carbon negative electrode material
CN116730322A
Negative electrode material and preparation method and application thereof
CN116936811A
Nitrogen and lithium doped porous carbon and silicon carbon composite material and preparation method and application thereof
CN117832447A